1987
DOI: 10.1111/j.1550-7408.1987.tb03183.x
|View full text |Cite
|
Sign up to set email alerts
|

Serology of Naegleria fowleri and Naegleria lovaniensis in a Hospital Survey1

Abstract: An avidin-biotin horseradish peroxidase method was used to detect antibodies to Naegleria fowleri and N. lovaniensis in human serum samples. Antibodies were detected in 101 specimens from 115 hospital patients ranging in age from 15 to 98 years. Class-specific anti-immunoglobulins identified antibodies as IgG and IgM. IgG antibody titers to both species ranged from 1:20 to 1:640. Seven of 15 serum samples collected from newborn infants also demonstrated IgG antibodies to these organisms with a titer range of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 37 publications
1
7
1
Order By: Relevance
“…The likely explanation for these antibodies in humans is contact with environmental amoebae. This conclusion is consistent with other surveys of antibody titers against Naegleria and Acanthamoeba species in humans and animals [2][3][4][5][8][9][10].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The likely explanation for these antibodies in humans is contact with environmental amoebae. This conclusion is consistent with other surveys of antibody titers against Naegleria and Acanthamoeba species in humans and animals [2][3][4][5][8][9][10].…”
Section: Discussionsupporting
confidence: 81%
“…Thus, it is not surprising that humans are exposed to them, as indicated by the presence of antiamoeba antibodies in serum. Antibody titers have been demonstrated for Naegleria [2][3][4], Acanthamoeba [2,5], and Balamuthia [6,7] species in surveys of healthy humans. Similarly, amoeba antibodies have been demonstrated in domestic [8] and wild animals [9,10].…”
mentioning
confidence: 99%
“…Although the antibody titers recorded have differed from study to study, almost all human sera from healthy individuals have been found to be positive for N. fowleri, indicating that exposure to the ameba is common. randomly obtained serum samples from hospitalized patients in the United States (Dubray et al, 1987). have been identified as a source of 'humidifier fever,' a nonlethal hypersensitivity reaction to inhaled antigenic material in recirculating water in humidifier systems (Edwards et al, 1976).…”
Section: Humoral Immunitymentioning
confidence: 99%
“…Because the major location of infection is the central nervous system and because PAME progresses rapidly, diagnosis in the early stages is difficult (10). Previous studies of the detection of antibodies in infections with pathogenic free-living amoebae have been performed using various methods such as agglutination tests, immunofluorescence tests, and an enzyme-linked immunoelectrotransfer blot technique (5,6,15,20). Monoclonal antibodies to N. fowleri have been produced and used as probes for the identification of N. fowleri in brain sections of PAME patients and to distinguish pathogenic N. fowleri from other Naegleria species (16,21).…”
mentioning
confidence: 99%